Євроінтегративні орієнтири екологізації підприємництва в Україні - Колмакова, В. (Baltic International Academy, 2018)
Мета статті передбачає розгляд особливостей екологічного підприємництва в Україні та обґрунтувати економіко-правові основи і стратегічні напрямки його розвитку в контексті апроксимації законодавства України до права ЄС в сфері охорони навколишнього середовища. Пропозиції щодо підвищення ефективності екологічної підприємництва в умовах розвитку децентралізації управління і розгортання процесів євроінтеграції за рахунок активізації державно-приватного партнерства визначають новизну ісследованія. // The purpose of the article is to consider the features of environmental entrepreneurship in Ukraine and to substantiate the economic and legal bases and strategic directions of its development in the context of approximation of the legislation of Ukraine to the EU’s law in the field of environmental protection. The suggetions to improve the efficiency of environmental business in the context of decentralization of management development and the deployment of European integration processes through the intensification of public-private partnerships determine the novelty of the research.
Keywords: децентралізація; екологічне право; євроінтеграція; підприємництво; decentralization; environmental law; eurointegration; entrepreneurship